Design and Development of a Multifunctional Convertible Wheelchair in a Low-Income Country Context - Saraf Fariha Moula; Sumaiya Tabassum Sporsho; Nelima Azad Chanda; Md Doulotuzzaman Xames (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2023)
The objective of this study is to design and develop a mobility aid that performs three different functions to serve patients with a cost-effective space utilizing a wheelchair. The focus was to develop an affordable product considering the poor economic status of the targeted users. A convertible multifunctional wheelchair was developed that can be used as a stretcher and as a regular wheelchair, and it has a pair of crutches to assist in walking. The design and stress-strain analysis of the product was done using SolidWorks 2019. Then, the product was manufactured using the simplest available manufacturing tools and materials. It was possible to fabricate a prototype of this multifunctional at a very cheap cost of BDT 14,250 ($162 approximately). However, it is believed that in mass production, the unit cost can be reduced by 40-50%. The fabricated prototype was lightweight with an average weight of approximately 16 kg allowing it to be portable. The design specifications also ensure ergonomic comfort. It can be contended that this device can be a cost-effective solution for patients and public hospitals in Bangladesh and similar low-income countries.